Evaluation Of Thyroid Gland By High Resolution Ultrasonography - Aruna Ramchandra Pawar; Suhas Dadarao Alone (International Journal of Medical Research and Review, 2015)
Introduction: Many thyroid diseases can present clinically with one or more thyroid nodules. Such nodules represent a common and controversial clinical problem. Much of the nodular disease is clinically occult (less than 1.5cm) but can be readily detected by high resolution ultrasonography. Evaluation of gland is important to assess whether the thyroid is normal or abnormal. The main objective of our study was to evaluate the patients with clinically palpable thyroid lesions using high resolution ultrasonography and to evaluate it either solitary nodule or a multinodular goiter and to differentiate thyroidal from extrathyroidal mass .The ultimate goal was to establish the role of high resolution ultrasonogrqaphy as an adjunct to clinical evaluation, hormonal assay, FNAC, and histopahology in the diagnosis of thyroid pathologies. This is a prospective study of two years in which 60 patients were under consideration.Methods: All the patients of clinically palpable thyroid lesions were referred to us for ultrasonography examination. The patients were in the age group of 11 years to 60 years. The sonogrpahic findings were compared with clinical diagnosis. All patients underwent fine needle aspiration cytology and 19 patients underwent surgery.NoduleResults: Females were more commonly involved. Multinodular goitre and diffuse goitre were most common findings.Conclusion: Thus high resolution ultrasonography is important modality for detection and characterization of thyroid nodules and is highly sensitive in detecting small nodules, cervical lymphadenopathy, carotid sheath and strap muscle invasion, the specificity is low